Pola Pendidikan Keagamaan Pesantren dan Radikalisme: Studi Kasus Pesantren-pesantren di Provinsi Jambi - Mursalin, Ayub; Katsir, Ibnu (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2010)
Islamic boarding school has been recently exposed with negative issues: becoming a source of terrorists and teaching radical ideologies that will disrupt the nation security stabilization. This article encourages to reveal the fact behind those issues based on the pattern of education adopted at the Islamic education system. Five Islamic schools in the province of Jambi will be the data source. It shows that in one side, Islamic education curriculum tends to be an understanding of belief of the conservative religious-dogmatic, while on the other side, tends to be moderate principle. The subjects of Fikh, tafsir (interpretation), and akidah (belief) lead to a conservative attitude in religious issues and politics. While in the social field, the curriculum is taught in a moderate way. Meanwhile, the tutor or ustaz encourages students to have a conservative attitude in praying and partly in the political field. However, the tutor or ustaz does not encourage students to act radically.